PENGEMBANGAN BAHAN BELAJAR FLIPBOOK PADA MATERI REDOKS DAN ELEKTROKIMIA BERBASIS PENDEKATAN STEM-PjBL BERBANTUAN VIDEO PEMBELAJARAN - Deni Ainur Rokhim; Hayuni Retno Widarti; Fauziatul Fajaroh (Kwangsan: Jurnal Teknologi Pendidikan, 2020)
In high school, chemistry learning there are redox and electrochemistry topics that equip students knowledge about the development of science and technology. Redox and electrochemistry learning topics will be more effective and efficient if students learn independently through learning materials developed by the educator so that students master the competencies that have been determined. In addition, educators are required to be skilled in the use of 21st century media and technology, such as learning materials that are packaged in e-books. So far, learning materials that have not been integrated into the Science Technology Engineering and Mathematics-Project Based Leaning (STEM-PjBL) learning model have not been developed. At present, STEM-PjBL research is a trending topic. The purpose of this study was to develop and determine the feasibility of flipbook teaching materials on redox and electrochemistry materials based on the STEM-PjBL approach assisted with learning videos. The development method used in this study is the Brog and Gall development model which is limited to five stages. The result of this research and development is a product in the form of learning materials which refers to the syllabus of the 2013 curriculum. This product is the result of the validation of a chemist (lecturer) and two chemistry teachers on lesson material learning. The results of validation are 92.71% and 92.78% respectively, which means that the product produced is very feasible. Readability test conducted on 30 students of SMAN 3 Sidoarjo obtained an average percentage of eligibility of 98.30% with very feasible criteria. So, the development of this flipbook has fulfilled the needs and high usage feasibility. AbstrakPada pembelajaran Kimia SMA, terdapat materi pelajaran redoks dan elektrokimia yang ditujukan untuk membekali siswa dengan pengetahuan tentang perkembangan sains dan teknologi. Pembelajaran materi redoks dan elektrokimia akan lebih efektif dan efisien jika siswa belajar mandiri melalui bahan belajar yang dikembangkan sendiri oleh pendidik agar siswa menguasai kompetensi yang telah ditentukan. Selain itu, pendidik dituntut juga untuk terampil dalam penggunaan media dan teknologi abad 21 ini, seperti bahan belajar yang dikemas dalam bentuk e-book. Selama ini, belum dikembangkan bahan belajar yang terintegrasi ke dalam model pembelajaran Science Technology Engineering and Mathematics-Project Based Leaning (STEM-PjBL). Saat ini, penelitian STEM-PjBL menjadi trending topic. Tujuan dari penelitian ini adalah untuk mengembangkan dan mengetahui kelayakan bahan ajar flipbook pada materi redoks dan elektrokimia berbasis pendekatan STEM-PjBL berbantuan video pembelajaran. Metode pengembangan yang digunakan di dalam penelitian ini adalah model pengembangan Brog dan Gall yang terbatas sampai lima tahap. Hasil dari penelitian dan pengembangan ini adalah sebuah produk yang berupa bahan belajar yang mengacu pada silabus Kurikulum 2013. Produk ini merupakan hasil validasi seorang ahli kimia (dosen) dan dua orang guru kimia terhadap bahan belajar RPP. Hasil validasi secara berturut-turut menunjukkan persentase 92,71% dan 92,78% yang berarti produk yang dihasilkan sangat layak. Uji coba keterbacaan produk yang dilakukan terhadap 30 siswa SMAN 3 Sidoarjo diperoleh rata-rata persentase kelayakan sebesar 98,30% dengan kriteria sangat layak.  Jadi, pengembangan bahan belajar flipbook ini telah memenuhi kebutuhan dan kelayakan pemakaian yang tinggi.